PENGEMBANGAN VIDEO ANIMASI BERBASIS PROBLEM BASED LEARNING PADA MATA PELAJARAN PENDIDIKAN PANCASILA UNTUK SISWA KELAS III SEKOLAH DASAR DI KOTA SOLOK - Muchmaina, Nabilla; Desyandri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the suboptimal quality of planning and implementation of Pancasila Education learning, as well as the limited innovative and contextual learning media. Learning is still dominated by lecture methods and the use of conventional media, so that students are less active, easily bored, and have difficulty understanding abstract concepts. This study aims to develop a valid, practical, and effective animated video based on Problem Based Learning in the Pancasila Education subject for third-grade elementary school students in Solok City. This type of research is Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The developed media was validated by material experts, media experts, and language experts, then tested and implemented to determine the level of practicality and effectiveness. Practicality was measured through teacher and student response questionnaires, while effectiveness was measured through protests and posttests. This research was conducted at SDN 09 PPA as a trial school, SDN 02 Aro IV Korong and SDN 03 Kampung Jawa as implementation schools. The results of the study showed that the animated video obtained a validity of 93% (very valid). Practicality at the trial stage obtained 100% (teachers) and 87.05% (students) in the practical category with an N-Gain of 84.98% (high). At the implementation stage, the practicality was 95% (teachers) and 80.21% (students) in the practical category with an N-Gain of 94.8% (high) at SDN 02 Aro IV Korong and 100% (teachers) and 92.86% (students) in the practical category with an N-Gain of 76.9% (high). Thus, the animated video based on Problem Based Learning is proven to be valid, practical, and effective for use in the Pancasila Education subject for grade III Elementary School students in Solok City.